Outlook, Support and Involvement of Parents in the Specialized Educational Programs of their Child in Inclusive Settings - Heyrana, Jessie Eric Q.; Gultia, Riza R.; Sitoy, Regina E.; Capuno, Reylan G.; Espina, Raymond C.; Apas, Cherenlie G.; Tenerife, Janine Joy L.; Calasang, Veronica O.; Osorio, Reizel Lynn S.; Tagaan, Jona L.; Maraguinot, Pearly T. (Journal of Innovation in Education and Social Research, 2025)
This study explored the perspectives, support, and involvement of Filipino parents in the special education of their children within integrated learning environments at Talamban Elementary School. Using a descriptive-correlational research design, data were collected from 37 parents and 27 teachers through structured questionnaires. The findings revealed that both parents and teachers held generally positive views on inclusive education, particularly regarding socialization, academic success, and tolerance. However, concerns emerged about parents' understanding of Individualized Education Plans (IEPs) and the reduction of stigma. Filipino parents provided moderate support, mainly through emotional support and advocacy, while their engagement in technical areas and material support was limited. The study also found that parents were moderately involved in their children's education, with stronger involvement in home-based activities and less in school-based activities such as Parent-Teacher Associations (PTA). A significant gap in the perception of parental involvement was observed, with parents perceiving themselves as highly involved, while teachers viewed their involvement as more moderate. Furthermore, a strong positive correlation was found between parents' positive perspectives on inclusive education and their level of support, as well as with their degree of involvement. The study highlighted the need for clearer communication and structured support to improve collaboration between parents and schools in inclusive education.